PERKAWINAN BEDA AGAMA DITINJAU DARI UNDANG-UNDANG PERKAWINAN - Angela, Theresia Yacintha (LPPM STIH Awang Long, 2024)
Marriage is the right of all people in Indonesia. Humans are social creatures who always interact with other humans regardless of ethnicity, race or religion. This interaction makes each other feel caring and have the desire to live together. It's just that we as humans cannot choose who we feel and see the religion of each society. Interfaith marriages are still a problem because in Law no. 1 of 1974 concerning marriage, especially Article 2 paragraph (1), states that marriage is valid if it is carried out in accordance with each person's religion and beliefs. However, there is no article explicitly discussing interfaith marriages, so people feel there is a legal vacuum. The purpose of this article is to find out whether Law no. 1 of 1974 concerning Marriage causes violations of Human Rights. The methodology used in this research is Normative Juridical to update legal products in order to obtain legal certainty, the analysis approach is carried out descriptively. Marriage and Human Rights are two things that cannot be separated because creating a family and living together are human rights and are inherent from birth into the world. If marriage regulations violate human rights, then the regulations regarding marriage must be changed and adapted to human rights so that society does not experience a legal vacuum and its human rights can be fulfilled.